New Normal Learning Method Satisfaction Among University Students in the Post-Pandemic Period: A Myanmar Perspective - Tun, Phyo Min; Srisura, Benjawan; Srivallop, Atikom; Vararuth, Veerawan (Human Behavior, Development and Society, 2024)
E-learning has become the new normal learning method in the post-pandemic period around the globe, including Myanmar. The present study aimed to examine the satisfaction of Myanmar university students with the new normal learning method. The study utilized an inductive quantitative approach, and structural equation modeling (SEM) was employed to analyze the data. Data was collected from 262 Myanmar students who were studying locally and abroad. The results of the study indicated that e-learning trust was more critical than e-learning effectiveness (p < .001), while e-learning system quality was insignificant for e-learning satisfaction. In addition, e-learning trust and effectiveness were mediating variables between e-learning system quality and e-learning satisfaction. This study delivers valuable insights for educators and university facilitators to enhance students’ satisfaction with new normal learning methods.